A novel linear gradient carbon fiber array integrated square honeycomb structure with electromagnetic wave absorption and enhanced mechanical performances. (1st February 2023) - Cheng, Linhao; Si, Yuan; Ji, Zhengjiang; Xu, Jianhui; Dong, Jiachen; He, Zhiheng; Huang, Ruilin; Zheng, Lin; Yan, Leilei; Zheng, Xitao
Abstract: Aiming to enhance electromagnetic (EM) wave absorption and compressive properties of sandwich structure, a novel scheme of structure/function integrated design was proposed based on composite square honeycomb structure (SHS). By using the EM characteristic of carbon fiber (CF), a novel spoof surface plasmon polaritons (SSPPs) structure that serves as the core of EM wave absorption can be obtained through winding continuous CF wires around orthogonal honeycomb walls. Numerical simulation and experimental verification show that the interlocked SHS realizes broadband (5–20 GHz), multiangle (0-70°) and efficient (average over 90%) absorption performance for EM wave incident from all directions. In addition, to further improve its mechanical properties, polymethacrylimide (PMI) foam was cut and inserted into the space of honeycomb core, forming PMI foam-filled SHS. Out-of-plane compression result indicates that due to coupling effects between honeycomb walls and PMI foam, its specific stiffness and specific compressive strength can be dramatically increased by 42% and 121%, respectively. Therefore, based on its excellent EM wave absorption and mechanical performances, the proposed interlocked SHS is highly competitive in EM wave absorption and load-bearing applications.